Sustainable Mobility - Llamas, Bernardo; Ortega Romero, Marcelo F.; Sillero, Eugenia (IntechOpen, 2020)
The concept of sustainability is already applied in all industrial sectors. The fight against climate change therefore forces us to look for alternatives in the way we move. Different alternative fuels are discussed in this book: from liquid and gaseous biofuels to electricity. Moreover, waste to fuel processes are another option to produce a significant amount of fuels. In the spirit of this book, there is not only collecting different alternatives, but creativity is also promoted in the readers of this book, so that they take an active part of the solution necessary to reduce greenhouse gas emissions.